Failure of antiepileptic drugs in controlling seizures in epilepsy : What do we do next? (2015)
Medically intractable epilepsy is a clinical condition of concern that arises when a patient with epilepsy suffers seizures, despite a trial of two or more antiepileptic drugs (AEDs) suitable for the type of epilepsy that are prescribed at maximum tolerated doses, does not achieve control of seizures. This diagnosis could be related to cortical dysplasias. We report the case of a 5-year-old girl with a previous normal neurological development and no family history of epilepsy who presented with focal-type seizures at age 4. She started treatment by taking different AEDs for seizure control. She continued having frequent seizures that sometimes progressed to generalized seizures and status epilepticus. After a focal cortical resection performed in the area where interictal spikes were detected, the pathology confirmed a type IIb cortical dysplasia as the cause of the epilepsy. This article discusses cortical dysplasias as a cause of pharmacoresistant epilepsy and its treatment. © 2015 The Authors.